Pendidikan dan Pembinaan Rohani Anak Usia Dini di Era Digital Berdasarkan 2 Timotius 3:15 - Telaumbanua, Sozawato; Dakhi, Nella Novianti; Putri Ziliwu, Elmin Swarni (Sekolah Tinggi Teologi Real Batam, 2024)
Children's spiritual education and development must start from an early age. Introduction to Bible teachings from an early age is very necessary in the ever-growing digital era, so that children are not easily eroded by the influx of various values that conflict with the Bible. Education and spiritual formation for early childhood must of course be adapted to the current context. The author will discuss the impact of fast access to information for children, the various challenges of implementing current spiritual values, the importance of using technology wisely, and the opportunities and risks associated with the use of digital technology. To answer this problem, in this research the author uses a qualitative method through literature study, which involves comparing various literature, be it books, articles or journals that are relevant to the topic of discussion. The main aim of this research is for parents and teachers to be able to introduce Bible teachings to children from an early age so that they are ready to face the challenges of today's digital era. The results of this research show that collaboration is needed from various parties, both parents and teachers, in providing education and spiritual formation for children in order to give birth to a generation of Christians who are strong and steadfast in Christian values amidst the ever-growing flow of digital technology. Keywords: Early Childhood; Digital Era; Coaching; Spiritual EducationAbstrakPendidikan dan pembinaan rohani anak harus dimulai sejak usia dini. Pengenalan ajaran Alkitab sejak dini sangat dibutuhkan di era digital yang terus berkembang, sehingga anak-anak tidak mudah tergerus dengan derasnya berbagai nilai yang bertentangan dengan Alkitab. Pendidikan dan pembinaan rohani anak usia dini tentunya harus disesuaikan dengan konteks saat ini. Penulis akan membahas mengenai dampak akses cepat terhadap informasi bagi anak-anak, berbagai tantangan menerapkan nilai-nilai rohani saat ini, pentingnya penggunaan teknologi secara bijaksana, dan peluang serta resiko yang terkait dengan penggunaan teknologi digital. Untuk menjawab permasalahan tersebut, maka dalam penelitian ini penulis menggunakan metode kualitatif melalui studi kepustakaan, yang melibatkan perbandingan berbagai literatur, baik itu buku-buku, artikel, maupun jurnal yang relevan dengan topik pembahasan. Tujuan utama penelitian ini adalah agar orang tua dan guru mampu memperkenalkan ajaran Alkitab bagi anak sejak usia dini agar mereka siap menghadapi tantangan di era digital saat ini. Hasil penelitian ini memperlihatkan bahwa dibutuhkan kolaborasi dari berbagai pihak, baik orang tua maupun guru dalam memberikan pendidikan dan pembinaan rohani bagi anak guna melahirkan generasi Kristen yang kuat dan teguh pada nilai-nilai Kristiani di tengah arus teknologi digital yang terus berkembang.Kata Kunci: Anak Usia Dini; Era Digital; Pembinaan; Pendidikan Rohani